2010
DOI: 10.4314/ajnt.v3i2.58892
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cytotoxin-Associated Gene Product-A Positive <i>Helicobacter Pylori</i> Strains on Micro-albuminuria in Type 2 Diabetes

Abstract: Introduction: Available data on the possible association between Helicobacter pylori (H. pylori) infection and diabetes mellitus (DM) are contradictory. The prevalence of cytotoxin associated gene product A (cagA) positive H. pylori is high in Egypt. This study aims to examine its association with type 2 DM, and its effect on glycemic control and the occurrence of microalbuminuria. Methods:The study involved 98 dyspeptic type 2 diabetic patients and 102 dyspeptic non-diabetic subjects who underwent upper gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…It was reported that H. pylori infection in Asians was predominated by CagA iceA1 genotypes while Americans and Africans by CagA iceA2 genotypes [ 41 , 43 ]. CagA is a major virulence factor of H. pylori and has been reported to be associated with diabetic complications [ 44 ]. CagA -positive strain of H. pylori could cause poor glycemic control in T2DM and difficulty in eradication, which might result in the visible H. pylori effect among Asian but not African DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that H. pylori infection in Asians was predominated by CagA iceA1 genotypes while Americans and Africans by CagA iceA2 genotypes [ 41 , 43 ]. CagA is a major virulence factor of H. pylori and has been reported to be associated with diabetic complications [ 44 ]. CagA -positive strain of H. pylori could cause poor glycemic control in T2DM and difficulty in eradication, which might result in the visible H. pylori effect among Asian but not African DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to Horikawa et al[ 151 ], the glycemic control of patients with DM was worse in the presence of H. pylori infections, in particular in infections with CagA-positive strains. A few studies demonstrated that eradication could lead to a benefit for glycemic control[ 152 , 153 ]. This has not been confirmed by other studies[ 154 ].…”
Section: Metabolic Diseasesmentioning
confidence: 99%
“…Vafaeimanesh et al[ 160 ] have demonstrated the existence of an association between diabetic patients with microalbuminuria and H. pylori infection. Microalbuminuria, as well as neuropathy and heart disease, are very common complications in patients with DM, and patients with CagA-positive H. pylori infection are at a greater risk of developing these complications[ 152 , 161 ].…”
Section: Metabolic Diseasesmentioning
confidence: 99%
“…Many inflammatory mediators were thought to be involved in the pathogenic way of extra digestive disorders caused by Helicobacter pylori infection which include; leukotriene C4, interleukin-1 (IL-1), interferon-(IFN)-γ), interleukin-6(IL-6), platelet-activating factor and tumor necrosis factor alpha-(TNF-α). [10] Proteinuria is a well-known indicator for renal disorders. The relationship between nephrotic range proteinuria (nephrotic syndrome) and hypoalbuminemia, edema, hyperlipidemia, susceptibility to infection, and hypercoagulability state also had been approved.…”
Section: Introductionmentioning
confidence: 99%